Honokiol decreases alpha-synuclein mRNA levels and reveals novel targets for modulating alpha-synuclein expression - Fagen, Sara J.; Burgess, Jeremy D.; Lim, Melina J.; Amerna, Danilyn; Kaya, Zeynep B.; Faroqi, Ayman H.; Perisetla, Priyanka; DeMeo, Natasha N.; Stojkovska, Iva; Quiriconi, Drew J.; Mazzulli, Joseph R.; Delenclos, Marion; et al. (Frontiers in Aging Neuroscience, 2023)
Background Intracytoplasmic inclusions comprised of aggregated alpha-synuclein (αsyn) represent a key histopathological feature of neurological disorders collectively termed “synucleinopathies,” which includes Parkinson’s disease (PD). Mutations and multiplications in the SNCA gene encoding αsyn cause familial forms of PD and a large body of evidence indicate a correlation between αsyn accumulation and disease. Decreasing αsyn expression is recognized as a valid target for PD therapeutics, with down-regulation of SNCA expression potentially attenuating downstream cascades of pathologic events. Here, we evaluated if Honokiol (HKL), a polyphenolic compound derived from magnolia tree bark with demonstrated neuroprotective properties, can modulate αsyn levels in multiple experimental models. Methods Human neuroglioma cells stably overexpressing αsyn, mouse primary neurons, and human iPSC-derived neurons were exposed to HKL and αsyn protein and SNCA messenger RNA levels were assessed. The effect of HKL on rotenone-induced overexpression of αsyn levels was further assessed and transcriptional profiling of mouse cortical neurons treated with HKL was performed to identify potential targets of HKL. Results We demonstrate that HKL can successfully reduce αsyn protein levels and SNCA expression in multiple in vitro models of PD with our data supporting a mechanism whereby HKL acts by post-transcriptional modulation of SNCA rather than modulating αsyn protein degradation. Transcriptional profiling of mouse cortical neurons treated with HKL identifies several differentially expressed genes (DEG) as potential targets to modulate SNCA expression. Conclusion This study supports a HKL-mediated downregulation of SNCA as a viable strategy to modify disease progression in PD and other synucleinopathies. HKL has potential as a powerful tool for investigating SNCA gene modulation and its downstream effects.